2015
DOI: 10.2105/ajph.2014.302309
|View full text |Cite
|
Sign up to set email alerts
|

Labor Unions: A Public Health Institution

Abstract: Using a social-ecological framework, we drew on a targeted literature review and historical and contemporary cases from the US labor movement to illustrate how unions address physical and psychosocial conditions of work and the underlying inequalities and social determinants of health. We reviewed labor involvement in tobacco cessation, hypertension control, and asthma, limiting articles to those in English published in peer-reviewed public health or medical journals from 1970 to 2013. More rigorous research i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 107 publications
0
33
0
Order By: Relevance
“…Differences in injury incidence could also reflect the distribution and effectiveness of safety programs and practices in a given industrial sector. Sectors might value and practice safety differently, on average, if targeted regulatory enforcement, differential insurance premiums, safety climate, average establishment size, or labor union involvement in occupational safety are strong enough incentives to influence sector‐wide safety practices. It is possible that industries, including manufacturing, with a history of readily apparent hazards likely to cause premature death have, over time, developed hazard mitigation strategies that include same‐level fall prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in injury incidence could also reflect the distribution and effectiveness of safety programs and practices in a given industrial sector. Sectors might value and practice safety differently, on average, if targeted regulatory enforcement, differential insurance premiums, safety climate, average establishment size, or labor union involvement in occupational safety are strong enough incentives to influence sector‐wide safety practices. It is possible that industries, including manufacturing, with a history of readily apparent hazards likely to cause premature death have, over time, developed hazard mitigation strategies that include same‐level fall prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Two workers said they had friends employed at pharmacies who provided information about what condoms to buy. Malinowski et al (2015) have analyzed labor unions as a public health institution and explored the role of unions in initiating public health policies. In the same vein, several scholars have noted how the decline of unions is a threat to public health (Wright 2016).…”
Section: Construction Workersmentioning
confidence: 99%
“…One such structural factor—declining labor union density—has precipitated burgeoning income inequity . Unionism's disproportionate decline among racialized, less‐educated, and blue‐collar workers, and the well‐documented relationship between unions and wages, benefits, occupational safety, and protective policies suggests a connection with growing mortality inequities . Thus, in this state‐level study, we analyzed union density's relationship with all‐cause mortality and overdose/suicide mortality, and tested whether declining union density has exacerbated racial and educational mortality inequities.…”
Section: Introductionmentioning
confidence: 99%
“…Unions may also protect health and reduce health inequities. At the workplace level, by regulating the balance of power between workers and management, unionization may reduce exposure to material deprivation (eg, inadequate wage and nonwage benefits, including access to health insurance and drug treatment), occupational hazards (eg, toxic chemicals), and stressors (eg, job instability or a lack of job autonomy), which can cause chronic disease and occupational injury, as well as mental illness, drug use, and their sequelae, like suicide and fatal overdose . For example, Hagedorn et al found that collectively bargained, legally binding union contracts tend to contain provisions promoting workers’ income, benefits, working‐time arrangements, safety, and decision‐making power .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation